THE LINGUISTIC PICTURE OF THE WORLD AND ITS THEORETICAL JUSTIFICATION - Atadjanova, Gulbaxar Yusupovna; Atadjanova , Gulbaxar Yusupovna (Educational Research in Universal Sciences, 2023)
Russian language picture of the world through the prism of phraseological units based on the material of modern Russian prose, which is based on the study of the structure and semantics of the expression of phraseological units at various levels of the language. The article consists in the fact that it undertakes a study of the Russian linguistic picture of the world through the prism of phraseological units on the material of modern Russian prose. The linguistic picture of the world carries the national mental traits of the people and is expressed by means of linguistic combinations, concepts and phraseological units.